Implementasi Framework Codeigniter Pada Perancangan Chatbot Interaktif Menerapkan Metode Waterfall - Cahya, Nilam; Triayudi, Agung; Benrahman, Benrahman (STMIK Budi Darma, 2021)
In delivering information related to lecture activities at the National University, the Information Systems Study Program has prepared a special website, namely http://si.ftki.unas.ac.id/. The website contains a lot of information about important activities or announcements, it's just that the need for other supporting information makes users have the need to ask further questions regarding the information contained on the website. Actually the Website http://si.ftki.unas.ac.id/ has provided the RoomChat feature for question and answer sessions between admin and users, but this feature is still ineffective, such as there is a time lag between questions and responses or unable to provide services for 24 jam. In this study, the authors wanted to design the chatbot feature using the waterfall method, which was carried out sequentially starting from the planning, analysis, design, implementation, testing to maintenance stages. While working on the application, this chatbot was created using the Codeigniter framework with the mysqli database. This chatbot feature will result in a more interactive question and answer session, so that two-way communication with users can run smoothly.